1988
DOI: 10.1111/j.1365-2621.1988.tb10214.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical Properties of Native and Heat Denatured Ovalbumin

Abstract: Affinity antibodies purified against native ovalbumin were found more reactive (higher avidity) against heat-denatured ovalbumin than against the native molecule by three different immunochemical methods. Quantitative immunoprecipitation in soluble phase revealed that more antigen-antibody complexes were insoluble with native ovalbumin than with heat-denatured ovalbumin; 25% of antibodies were still present in supernatant at equivalence as measured by ELISA. At the same conditions with heat-denatured ovalbumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…The allergenicity of OA was changed by heating or pepsin treatment. The primary structure of OA is not changed by heating [18] or pepsin treatment [10] [20]. Breton et al described that native OA was found as a single band of 45 kd, and heat-denatured OA was also found as a single band of 45 kd as judged by SDS-PAGE analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The allergenicity of OA was changed by heating or pepsin treatment. The primary structure of OA is not changed by heating [18] or pepsin treatment [10] [20]. Breton et al described that native OA was found as a single band of 45 kd, and heat-denatured OA was also found as a single band of 45 kd as judged by SDS-PAGE analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Commercial products are available for a few selected applications only, e.g. ovalbumin from eggs [19]. Before detection with the specific antibodies, immunoanalytical determinations require appropriate sample preparation.…”
Section: Immunoanalytical Techniquesmentioning
confidence: 99%
“…Similar results have been reported in several other studies. Breton et al (1988) demonstrated that, when determined by ciELISA using anti-OA antibody, the detection limit of heat-denatured OA was 0.01 µg/mL although that of native OA was 0.1 µg/mL. They explained these results as follows during heat denaturation, OA can form new epitopes that are available to anti-OA antibody with the same specificity as those detected on the native structure of the antigen.…”
Section: Resultsmentioning
confidence: 84%
“…This change can affect antibody recognition toward antigen proteins (Breton et al, 1988;Samarajeewa et al, 1991). Therefore, we attempted to develop a reliable ELISA system for the quantification of egg proteins, regardless of heat treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation